Recognizing the Molecular Multifunctionality and Interactome of TIMP-1. Issue 1 (January 2019) - Grünwald, Barbara; Schoeps, Benjamin; Krüger, Achim
Abstract : Tissue inhibitor of metalloproteinase 1 (TIMP-1) is a major player in preserving tissue integrity and has recently also emerged as a decisive factor in several human pathologies. This appreciation has prompted this review addressing the largely underestimated complexity of the functions executed by TIMP-1 and their mechanistic basis. In fact, the versatile impact of TIMP-1 on cellular functions stems from its two-domain structure harboring metalloproteinase-inhibitory and cytokine-like signaling activities. This feature leads to functional interactions with numerous and distinct enzymatic and cell-surface proteins that initiate an exceptionally broad range of downstream effects. We propose here that this multifunctionality and the remarkably large interactome explain the diverse biological consequences of TIMP-1 expression in health and disease. Highlights: TIMP-1 controls major aspects of cell biology, and its deregulation contributes to various diseases such as inflammation, fibrosis, and cancer. However, functional misconceptions still hamper our understanding of its precise molecular role in complex contexts. TIMP-1 is a two-domain protein with multiple functions, and the list of its interaction partners has rapidly expanded in recent years. This review develops the first integrated view of multifunctionality as an important biological feature of TIMP-1. We propose that TIMP-1 is a regulatory hub in an exceptionally large protein-interaction network, and highlight several highly context-specific regulatory mechanisms that can affect the molecular mode of action of TIMP-1. Appreciation of the interrelated functions of TIMP-1 as a protease inhibitor and signaling molecule facilitates integration of previously contradictory findings. This may aid the development of precise TIMP-1-directed therapeutic strategies and serve as a role model for other multifunctional proteins and their impact on cell biology.